PERAN PENDIDIKAN DALAM PENGEMBANGAN KARAKTER 5.0 - Miftahul Jannah Putri Husma; Shaleh Shaleh; Tutut Handayani (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2023)
Abstract Education has a close relationship with the teaching and learning process and school is the place where learning takes place. In the learning process, the main elements that must exist are teachers and students. For the elementary school level, the teacher is the main source of learning, although in practice the role of the teacher can be replaced by using instructional media. Thus, in the latest educational curriculum implemented in Indonesia, teachers can also be referred to as facilitators in learning. The purpose of this study is to analyze the importance of the role of education in developing character 5.0. The method used is qualitative. The results obtained are that the role of education in developing character 5.0 is very important. The role of education in character development 5.0 can be carried out with the synergy of informal, non-formal and formal education which are interrelated with one another. Provision of good education which is based on national education goals will create character education that is independent, intelligent, moderate, and has a religious spirit